Infectious and tropical diseases : a handbook for primary care - Kwan-Gett, Tao Sheng Clifford; Kemp, Charles;Kovarik, Carrie (St. Louis, Missouri : Elsevier Mosby, 2006)
This practical reference provides a single, concise source of current information on the diseases and conditions common among immigrants, refugees, travelers, and persons in contact with these populations in the developed world. An easy-to-use format makes this reference ideal for primary care and other providers in a variety of clinical settings. It also features content on agents that may be used as biological warfare.
Introduction to infectious diseases of immigrants, refugees, and travelers -- Classification of infectious diseases -- Diagnosis and approaches to patients -- Actinomycosis -- Amebiasis -- Anisakidosis -- Anthrax -- Arbovirus encephalities -- Ascariasis -- Babesiosis -- Bartonellosis -- Blastomycosis -- Botulism -- Brucellosis -- Buruli ulcer -- Capillariasis -- Chagas' disease -- Chikungunya fever -- Cholera -- Chromoblastomycosis -- Coccidioidomycosis -- Cryptococcosis -- Cryptosporidiosis -- Cutaneous larva migrans -- Dengue -- Diphtheria -- Ebola and Marburg hemorrhagic fevers -- Echinococcosis -- Enterobiasis -- Filariasis: dracunculiasis -- Filariasis: loiasis -- Filariasis: lymphatic -- Filariasis: onchocerciasis -- Giardiasis -- Gnathostomiasis -- Granuloma inguinale -- Hantavirus hemorrhagic fever with renal syndrome -- Hantavirus pulmonary syndrome -- Hemorrhagic fevers, viral -- Hepatitis A -- Hepatitis B -- Hepatitis, non-A and non-B -- Histoplasmosis -- Hookworm -- Hymenolepiasis -- Lassa fever -- Leishmaniasis -- Leprosy -- Leptospirosis -- Lice, head -- Lyme disease -- Malaria -- Measles -- Melioidosis -- Meningitis, bacterial -- Mycetoma -- Myiasis -- Paracoccidioidomycosis -- Parastrongyliasis, abdominal -- Parastrongyliasis, meningitis -- Pemphigus, endemic foliaceus -- Pertussia -- Pinta -- Plague -- Poliomyelitis -- Psittacosis -- Q fever -- Relapsing fever -- Scabies -- Schistosomiasis -- Severe acute respiratory syndrome -- Smallpox -- Sporotrichosis -- Staphylococcal skin infection -- Strongylodiasis -- Syphilis -- Tapeworm -- Tetanus -- Tinea -- Toxocariasis -- Toxoplasmosis -- Trachoma -- Trematodes, hepatic -- Trematodes, intestinal -- Trematodes, pulmonary -- Trench fever -- Trichinellosis -- Trichuriasis -- Trypanosomiasis, African -- Tuberculosis -- Tularemia -- Tungiasis -- Typhoid and paratyphoid fevers -- Typhusv Yaws -- Yellow fever.
Includes bibliographical references and index.
Keywords: HANDBOOKS AND MANUALS